Students’ Perception of Teachers’ Reference Norm Orientation and Cheating in the Classroom - Marksteiner, Tamara; Nishen, Anna K.; Dickhäuser, Oliver (Frontiers in Psychology, 2021)
Students’ cheating is a serious problem: It undermines the chance to adequately promote, support, and evaluate them. To explain cheating behavior, research seldom focuses on perceived teachers’ characteristics. Thus, we investigate the relationship between students’ cheating behavior and an important teacher characteristic, individual reference norm orientation (IRNO; i.e., the tendency to evaluate students based on their performance development over time). We examined cheating on written exams, on homework, and in oral exams among N = 601 students (64.2% girls; Mage = 16.07 years) in N = 31 language classes. Results from doubly manifest multi-level analyses showed that, on the classroom level, cheating on written exams and on homework occurred less frequently the more the classroom of students perceived their teachers as having an IRNO. We found no further evidence for other cheating factors or student characteristics. This supports the idea that teacher characteristics are associated with some forms of students’ cheating behavior.